Тheory of Abu Mansur al-Maturidi’s epistemology (nazariat al-ma’rifa) - Akimkhanov, A. B. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The article describes theory of Abu Mansur al-Maturidi’s epistemology. Imam Maturidi is the first Muslim theologian to base his knowledge on the epistemology. That is why we have a ground to state that Maturid’s «Kitab at-Tauhid» among the classical Islamic books we have today is an ancient theological book which describes the epistemology, its subjects and objects in detail. Maturidi paid a special attention to epistemology as he aimed to create the religious and moral sysem based on the epistemology. In his opinion the real religiosity is not imitation, it is based on knowledge and facts.